2008
DOI: 10.1021/jm800626a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cathepsin K Inhibitors on Bone Resorption

Abstract: On the basis of the pyrrolopyrimidine core structure that was previously discovered, cathepsin K inhibitors having a spiro amine at the P3 have been explored to enhance the target, bone marrow, tissue distribution. Several spiro structures were identified with improved distribution toward bone marrow. The representative inhibitor 7 of this series revealed in vivo reduction in C-terminal telopeptide of type I collagen in rats and monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A number of related cathepsin K inhibitors with warhead group that covalently bind to active site Cys25 of cathepsin K have been identified [25][26][27][28][29][30][31][32][33][34]. The Merck group has recently reported that the electrophilicity and reactivity of nitrile-containing inhibitors, in three different chemical classes, has an impact on the reversibility of the enzymeinhibitor complex [38].…”
Section: High-throughput Screening (Hts): Identification Of the Purinmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of related cathepsin K inhibitors with warhead group that covalently bind to active site Cys25 of cathepsin K have been identified [25][26][27][28][29][30][31][32][33][34]. The Merck group has recently reported that the electrophilicity and reactivity of nitrile-containing inhibitors, in three different chemical classes, has an impact on the reversibility of the enzymeinhibitor complex [38].…”
Section: High-throughput Screening (Hts): Identification Of the Purinmentioning
confidence: 99%
“…Novel inhibitors possessing the P3 group derived from the spiro-hydantoin structure were prepared and the inhibitory potency for cathepsin K was evaluated as shown in Tables 6 and 7 [29]. Replacement of the P3 moiety with the reversed analogue of 41 resulted in the retention of potency and no substantial change in the selectivity against cathepsins L and S (41 vs 42).…”
Section: (4) the Third Step In Tackling The Optimization Of The Cathementioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the aldehyde inhibitors, a variety of inhibitors possessing a nitrile moiety as the warhead functions as mild electron deficient center and the functional group were introduced to many enzyme inihibitors. [12][13][14][15] In this area, we exerted effort to develop totally new chemotype plasmin inhibitors. On the basis of information on substrate specificity of plasmin, non-peptidic and peptidic plasmin inhibitors having the nitrile moiety as the warhead were first designed and prepared.…”
Section: Introductionmentioning
confidence: 99%